Hydrogen Embrittlement of A High Strength Low Alloy Pipeline Steel - Chung, Cheuk-Kwong (My University, 1980)
The effect of hydrogen has been studied on a grade X65 high strength low alloy (HSLA) pipeline steel using a four point bend test. Hydrogen was introduced into single V-notched test samples by a standard BP method. Slow bend tests were conducted on both the base metal and on the heat affected zone (HAZ) of a commercially welded plate. It was found that hydrogen reduced the plastic strain required for crack initiation and increased the rate of crack propagation in three orientations of the base metal and in one orientation of the HAZ. Tests using a higher strain rate, showed that hydrogen still promoted crack initiation but did not affect the rate of crack propagation. Metallographic examination indicated that the orientations of inclusions played an important role in determining the path of crack propagation and delamination.
Keywords: Metallurgy; Metallurgy